In the Track of R. L. Stevenson and Elsewhere in Old France - Hammerton, J. A. (John Alexander), 1871-1949 (Salt Lake City, UT : Project Gutenberg, 2013)
"In the Track of R. L. Stevenson and Elsewhere in Old France" by J. A. Hammerton is a travelogue written in the early 20th century. The book recounts the author's journey through various picturesque parts of France, particularly tracing the steps of the famous writer Robert Louis Stevenson during his own travels. It explores regions such as the Cevennes and delves into the natural beauty and historical sites of the French landscape. The beginning of the text introduces the author's reflections on storytelling and the personal connection many readers have with travel narratives. Hammerton expresses a desire to follow in Stevenson's footsteps, not merely to replicate his journeys but to experience the beauty and the essence of the places he loved. He reminisces about his own experiences in French villages, highlighting the unique character of the locals and the enduring charm of the landscapes. As he begins his trek from Le Puy, he shares vivid descriptions of his surroundings, including the memories of Stevenson s adventures, setting the stage for a rich exploration of both the physical journey and the emotional resonance tied to the experienced landscape. (This is an automatically generated summary.)
Release date is 2013-07-13
E-text prepared by Melissa McDaniel and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: France -- Description and travel; Stevenson, Robert Louis, 1850-1894 -- Travel -- France; Cévennes Mountains (France)